Folate shapes plant root architecture by affecting auxin distribution - Li, Y.; Luo, J.; Chen, R.; Zhou, Y.; Yu, H.; Chu, Z.; Ouyang, B.
Folate (vitamin B9)is important for plant root development, but the mechanism is largely unknown. Here we characterized a root defective mutant, folb2, in Arabidopsis, which has severe developmental defects in the primary root. The root apical meristem of folb2 mutant is impaired, and adventitious roots are frequently found at the root-hypocotyl junction. Positional cloning revealed that a 61-bp deletion is present in the predicted promoter - 5' untranslated region of AtFolB2, a gene encoding a dihydroneopterin aldolase that functions in folate biosynthesis. This mutation led to a significant reduction in the transcriptional level of AtFolB2. Liquid chromatography-mass spectrometry analysis showed that the content of the selected folate compounds was decreased in folb2. RNA interference lines wåith knocked down expression of AtFolB2 in Arabidopsis could phenocopy folb2 mutant. On the other hand, the application of exogenous 5-formyl tetrahydrofolic acid could rescue the root phenotype of folb2, indicating the root phenotype is indeed related to the level of folate. Further analysis revealed that folate could promote rootward auxin transport through auxin transporters, and that folate may affect particular auxin/indole-3-acetic acid proteins and auxin response factors. Our findings provide new insights into the important role of folic acid in shaping root structure.
Keywords: ATFOLB2; AUXIN; FOLATE; PIN REPORTER; ROOT DEVELOPMENT